(untitled) (Research, Society and Development, 2021)
Population growth demands new areas for the performance of human activities. However, these activities directly influence water quality and availability. This study was based on the hypothesis that the activities that make up the land use and cover scenario in a watershed in the municipality of. Can be causing a compromise in the surface water quality. To this end, the general objective of this work is to establish the relationship of influence of land use and cover of human activity on the conservation and water quality of Pau Amarelo watershed, in São Francisco do Pará - PA. It is proposed to diagnose the current situation of land use and land cover and to analyze the variables that guide the surface water quality of the Pau Amarelo Watershed, taking into account the homogeneity of the land use and land cover classes in the vicinity of the main course and stretch of land. tributaries of the watershed. The elaboration of a land use and occupation map in Geographic Information System - GIS software, aiming to relate the different scenarios with the water quality. Interpretation of the data led to the conclusion that land use and land cover in the Pau Amarelo watershed area is mostly integrated by Capoeira (48.1%) and Pastos (24.1%), followed by dense forest areas (9, 7%), cultivation (8.8%), built (3.03%), and other uses (6.3%). The results reveal a slight relationship between the multiple uses and land cover in the physicochemical and microbiological variables of water, a fact that does not provide a very well defined gradient of some variables analyzed. When submitting the parameters to the IQA analysis, it was observed that the monitoring point near the “exposed or built up soil area” presented the lowest index, while in areas classified as “capoeira” they allowed the IQA ancestry. The microbasin level study was able to represent the state of land use and its influence on water quality.